Computerized Reconstruction of Pulpal Blood Vessels Examined under Confocal Microscope - Digka Anna; Lyroudia Kleoniki; Kubinova Lucie; Karayannopoulou Georgia; Marras Ioannis; Pitas Ioannis (Balkan Stomatological Society, 2015)
The purpose of this study was the evaluation of 3 different histological methods for studying pulpal blood vessels in combination with 2 types of confocal microscope and computer assisted 3-dimensional reconstruction. 10 human, healthy, free of restorations or caries teeth that were extracted for orthodontic reasons were used. From these teeth, the pulp tissues of 5 were removed, fixed in formalin solution, dehydrated and embedded in paraffin. Serial cross sections 5μm thick were taken from 3 of the above mentioned pulpal tissues and stained with CD34 according to the immunohistochemical ABC technique, while the rest 2 were stained with CD34 and Cy5 by means of immunofluorescence after serial cross sectioning of 10μm. 5 of the 10 teeth were fixed, decalcified, serial cross sectioned (30μm thickness) and stained with eosin. The physical sections were examined under 2 types of confocal laser microscope. Serial images were taken for each section, alignment of the images was followed and finally 3-dimensional reconstructions of the pulpal vessels were achieved.